KONSELING DAN PSIKOTERAPI BAGI DEPENDENSI: Studi Di LSM Kelompok Kerja Pelita Hati Husada Banyuwangi - Yohandi Yohandi; A. Khairuddin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2015)
Drug abuse is part of the social problems that has got from studen. Cause the drug abuse is a violation of the sanctions severe enough, then obviously the addicts psychologically connect with anyone, worried that their identity and are known by the authorities. This study tries to explore what is done by the NGO Kelompok Kerja Pelita Harapan Banyuwangi that have provided counseling and psychotherapy services to his patients.Â